ONLINE SAFETY AND RISKS: INSIGHTS FROM SAUDI FEMALE STUDENTS AND MOTHERS - Jabali, Maha (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study investigates the digital engagement and online safety perceptions of Saudi female students aged 12 to 17, set against the backdrop of the Kingdom's unique socio-cultural context. Utilizing a mixed-methods approach that combines surveys and interviews, the research delves into internet usage patterns, device preferences, online activities, and perceptions of online risks and safety among this demographic. Key findings reveal that Saudi girls exhibit extensive internet use, with older adolescents particularly active during weekends and holidays. The home predominates as the primary internet access point, with smartphones being the device of choice. Online activities span entertainment, education, socialization, community participation, creative expression, and commercial interactions, highlighting a multifaceted digital engagement. Concerns about online risks, including exposure to inappropriate content, interactions with strangers, and cyber threats, are prevalent among both girls and their mothers, with mothers typically perceiving the internet as less safe. Despite these concerns, the study uncovers a robust support system for online safety at home and in schools, with parents, especially mothers, playing a crucial role in mediation, alongside varying degrees of school involvement. The findings underscore the complex interplay between digital engagement, perceived online risks, and safety mediation strategies within the Saudi context. They emphasize the need for comprehensive online safety education and tailored interventions that resonate with the cultural and developmental realities of young Saudi girls. This research contributes to the global discourse on youth digital engagement, offering insights into the nuanced digital experiences of Saudi girls and the pivotal role of familial and educational support in navigating the digital landscape safely and effectively.